Huntingtin-Interacting Protein 1-Related Protein Plays a Critical Role in Dendritic Development and Excitatory Synapse Formation in Hippocampal Neurons - Peng, Lin; Yang, Qian; Xu, Xingxing; Du, Yonglan; Wu, Yu; Shi, Xiaofang; Xu, Junyu; Zhu, Lijun; Luo, Jianhong (Frontiers in Molecular Neuroscience, 2017)
Huntingtin-interacting protein 1-related (HIP1R) protein is considered to be an endocytic adaptor protein like the other two members of the Sla2 family, Sla2p and HIP1. They all contain homology domains responsible for the binding of clathrin, inositol lipids and F-actin. Previous studies have revealed that HIP1R is highly expressed in different regions of the mouse brain and localizes at synaptic structures. However, the function of HIP1R in the nervous system remains unknown. In this study, we investigated HIP1R function in cultured rat hippocampal neurons using an shRNA knockdown approach. We found that, after HIP1R knockdown, the dynamics and density of dendritic filopodia, and dendritic branching and complexity were significantly reduced in developing neurons, as well as the densities of dendritic spines and PSD95 clusters in mature neurons. Moreover, HIP1R deficiency led to significantly reduced expression of the ionotropic glutamate receptor GluA1, GluN2A, and GluN2B subunits, but not the GABAA receptor α1 subunit. Similarly, HIP1R knockdown reduced the amplitude and frequency of the miniature excitatory postsynaptic current, but not of the miniature inhibitory postsynaptic current. In addition, the C-terminal proline-rich region of HIP1R responsible for cortactin binding was found to confer a dominant-negative effect on dendritic branching in cultured developing neurons, implying a critical role of cortactin binding in HIP1R function. Taken together, the results of our study suggest that HIP1R plays important roles in dendritic development and excitatory synapse formation and function.